ANALISIS KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS VII SMP NEGERI 2 RANCAKALONG - Nanang Supriatna; Yusfita Yusuf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the numeracy literacy skills of seventh-grade students at SMP Negeri 2 Rancakalong. Numeracy literacy is a fundamental skill necessary for understanding and applying mathematical concepts in daily life. This research uses a qualitative method with a descriptive approach. The research sample consists of 30 students selected through purposive sampling. Data were collected through a numeracy literacy test, which includes three main indicators: number understanding, data interpretation, and solving numerical problems. The results show that the majority of students fall into the "sufficient" (33.33%) and "low" (30%) categories, with an overall average score of 45. Although there are a few students in the "good" and "very good" categories, their numbers are relatively small (6.67%). Factors contributing to the low numeracy literacy skills include a lack of connection between the test questions and real-life contexts, low learning motivation, and teaching methods that remain too theoretical. This study recommends the implementation of context-based learning, the use of technology in education, and training for teachers to enhance students' numeracy literacy. The findings of this study are expected to contribute to the development of more effective teaching strategies to improve numeracy literacy at the primary education level.